Effects of mangosteen peels on in vitro rumen fermentation and methane production in goats - Ishak, Izdihar (2015)
The effect of mangosteen peels (MP) on rumen fermentation and methane production were evaluated using an in vitro gas production technique. Three groups were designed which comprised a control group without MP (50% concentrate + 50% alfalfa), medium mangosteen peel (MMP) (50% concentrate + 25% alfalfa+ 25% mangosteen peel) and high mangosteen peel (HMP) (50% concentrate + 50% mangosteen peel) group. The in vitro fermentation was carried out in 100ml sealed syringes that contained 0.25g of dried feed materials and 30ml of rumen fluid incubated at 39°C for 24 hours. The total gas production over 24 hours showed no significant difference (p>0.05) between groups although the supplemented groups with MP showed lesser total gas production. The rate of gas production also showed a lower rate for MMP and HMP groups compared to control group although it was not significantly different (p>0.05). The volatile fatty acid production, pH and ammonia nitrogen showed no significant difference between all treatment groups. However, methane production in both MP groups was significantly lower (p<0.05) than the control after 24 hours of incubation. The MP supplementation reduced the total bacterial population significantly (p<0.05) in the HMP group compared to MMP and control groups. The population of total methanogenic bacteria was significantly reduced (p<0.05) in the two groups supplemented with MP. However, there was no significant difference (p>0.05) in the protozoal population between all the groups. In conclusion, supplementation of goat diets with mangosteen peels under in vitro conditions showed no adverse effects on rumen fermentation parameters but reduced the population of methanogenic bacteria hence reducing the methane production which should reduce environmental pollution.